PROTECTION OF MELINTING DANCE AS HERITAGE CULTURE FROM LAMPUNG SOCIETY CUSTOM IN THE PERSPECTIVE OF INTELLECTUAL PROPERTY LAW SYSTEM - Reza Aditya Ramadhan (Indonesia Private Law Review, 2020)
The existence of Melinting Dance as a traditional dance from East Lampung Regency does not get maximum protection against local communal intellectual property. The problem in this article is What is the protection of intellectual property law against Traditional Cultural Expressions? What is the role of the Lampung provincial government in protecting intellectual property against the communal rights of the traditional dance of Lampung Province? This research is intended to find a model of protection for the Melinting Dance. This research uses a Normative and Empirical Juridical approach.